Peculiarities and Consequences of Different Angiographic Patterns of STEMI Patients Receiving Coronary Angiography Only: Data from a Large Primary PCI Registry - Alexandru Burlacu; Grigore Tinica; Bogdan Artene; Paul Simion; Diana Savuc; Adrian Covic (Emergency Medicine International)
Background. Inappropriate cardiac catheterization lab activation together with false-positive angiographies and no-culprit found coronary interventions are now reported as costly to the medical system, influencing STEMI process efficiency. We aimed to analyze data from a high-volume interventional centre (>1000 primary PCIs/year) exploring etiologies and reporting characteristics from all “blank” coronary angiographies in STEMI. Methods. In this retrospective observational single-centre cohort study, we reported two-year data from a primary PCI registry (2035 patients). “Angio-only” cases were assigned to one of these categories: (a) Takotsubo syndrome; (b) coronary embolisation; (c) myocardial infarction with nonobstructive coronary arteries; (d) myocarditis; (e) CABG-referred; (f) normal coronary arteries (mostly diagnostic errors); and (g)others (refusals and death prior angioplasty). Univariate analysis assessed correlations between each category and cardiovascular risk factors. Results. 412 STEMI patients received coronary angiography “only,” accounting for 20.2% of cath lab activations. Barely 77 patients had diagnostic errors (3.8% from all patients) implying false-activations. 40% of “angio-only” patients (n = 165) were referred to surgery due to severe atherosclerosis or mechanical complications. Patients with diagnostic errors and normal arteries displayed strong correlations with all cardiovascular risk factors. Probably, numerous risk factors “convinced” emergency department staff to call for an angio. Conclusions. STEMI network professionals often confront with coronary angiography “only” situations. We propose a classification according to etiologies. Next, STEMI guidelines should include audit recommendations and specific thresholds regarding “angio-only” patients, with specific focus on MINOCA, CABG referrals, and diagnostic errors. These measures will have a double impact: a better management of the patient, and a clearer perception about the usefulness of the investments.